Complete electrochemical dechlorination of chlorobenzenes in the presence of various arene mediators - A. Jalil, Aishah; Triwahyono, Sugeng; M. Razali, N. Aini; H. Hairom, N. Hanis; Idris, Ani; M. Muhid, M. Nazlan; Ismail, Azlyana; M. Yahaya, N. Aisyah; L. Ahmad, N. Akma; Dzinun, Hazlini (Elsevier, 2010)
Electrochemical dechlorination of chlorobenzenes in the presence of various arene mediators such as naphthalene, biphenyl, phenanthrene, anthracene, and pyrene, was studied. The amount of mediator required was able to be reduced to 0.01 equiv. for all mediators except for anthracene, with the complete dechlorination of mono-, 1,3-di- and 1,2,4-trichlorobenzene still achieved. This catalytic amount of mediator plays an important role in accelerating the dechlorination through the rapid formation of radical anions prior to reduction of the chlorobenzenes.